READING KARA’S NEEDS IN PAMELA CLARE’S EXTREME EXPOSURE - Wenanda, Diva; Ayuningtias, Diah Ikawati; Inayati, Rif'ah (Jurusan Sastra Indonesia, 2023)
This study focuses on the motivation which motivate Kara wants to fulfill her needs in Pamela Clare’s Extreme Exposure. This study aims to explain the motivations of the main character to fulfill her needs which are taken from Extreme Exposure Novel written by Pamela Clare. This study is conducted by applying a qualitative research design since the data are in the form of words. The data of this study are the utterances which contain of Kara’s motivations to fulfill her needs in the novel Extreme Exposure. The data are collected by using content analysis method. In analyzing the data, the writer uses interactive data analysis. This study uses Human Motivation by Abraham Maslow, known as “The Hierarchy of Needs”.It reveals the aspect of the main character’s motivation to fulfill her needs. Kara has strong motivation from her unpleasant experiences in the past that are, Kara’s father and boyfriend left her, and Kara’s love her son. From her unpleasant experiences, make Kara wants to reach what she needs in sexual needs, protection, love and belongingness, Kara’s self esteem and her desire of job as her self actualization.